Pengaruh Pola Asuh Uninvolved Terhadap Kondisi Emosi Anak di Jorong Seberang Mimpi Kenagarian Gunung Medan Kabupaten Dharmasraya - Rahayu, Kiki Silvia; Yusri, Fadhilla; Afrinaldi; Kamal, Muhiddinur (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2024)
This research is motivated by the application of uninvolved parenting by parents to their children. towards children. The characteristics of this parenting pattern include ignoring children who come home late at night or don't come home for more than one day, and lack of parental involvement. late at night or not coming home for more than one day, and paying less attention to their appearance when going to school. children's appearance when going to school. Children with this parenting style children often experience emotional problems such as fighting at school or home, yelling at parents, speaking harshly, and damaging things when emotional. This study is a correlative quantitative study that aims to determine the influence between uninvolved parenting and children's emotional conditions. The study population was children aged 7-12 years in Jorong Seberang Mimpi Kenagarian Gunung Medan, Dharmasraya Regency, with a sample of 23 children selected by purposive sampling. selected by purposive sampling. Data were collected using a Likert scale and processed with non-parametric regression test using SPSS Version 22. The results showed a regression equation of Ý = 181.373 + 0.975X, which means that every 1% increase in uninvolved parenting will increase children's emotional state by 0.975. children's emotions by 0.975. Hypothesis testing showed a significant effect of uninvolved parenting on children's emotional condition is 77%, while 23% is influenced by other factors. influenced by other factors. Abstrak Penelitian ini dilatarbelakangi oleh penerapan pola asuh uninvolved oleh orang tua terhadap anak. Ciri-ciri pola asuh ini termasuk mengabaikan anak yang pulang larut malam atau tidak pulang selama lebih dari satu hari, dan kurang memperhatikan penampilan anak saat pergi ke sekolah. Anak-anak dengan pola asuh ini sering mengalami masalah emosi seperti bertengkar di sekolah atau rumah, membentak orang tua, berkata kasar, dan merusak barang-barang saat emosi. Penelitian ini adalah penelitian kuantitatif korelatif yang bertujuan untuk mengetahui pengaruh antara pola asuh uninvolved dan kondisi emosi anak. Populasi penelitian adalah anak usia 7-12 tahun di Jorong Seberang Mimpi Kenagarian Gunung Medan Kabupaten Dharmasraya, dengan sampel 23 anak yang dipilih secara purposive sampling. Data dikumpulkan menggunakan skala likert dan diolah dengan uji regresi non parametrik menggunakan SPSS Versi 22. Hasil penelitian menunjukkan persamaan regresi Ý = 181.373 + 0,975X, yang berarti setiap peningkatan 1% dalam pola asuh uninvolved akan meningkatkan kondisi emosi anak sebesar 0,975. Uji hipotesis menunjukkan pengaruh signifikan pola asuh uninvolved terhadap kondisi emosi anak sebesar 77%, sementara 23% dipengaruhi oleh faktor lain.